Characterization of the intestinal absorption of inorganic mercury in Caco-2 cells. Issue 1 (February 2015) - Vázquez, M.; Devesa, V.; Vélez, D.
Highlights Mechanisms of intestinal transport of Hg(II) has been evaluated using Caco-2 cells. Hg(II) can be considered a compound with a moderate absorption. Transport takes place mainly by carrier-mediated mechanisms with an active component. Divalent cation, amino acids, and organic anion transporters could participate. An important cellular accumulation of up to 51% has been observed.